1997
DOI: 10.1200/jco.1997.15.8.2945
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with aggressive non-Hodgkin's lymphoma: disease presentation, response to treatment, and survival--a Groupe d'Etude des Lymphomes de l'Adulte study on 453 patients older than 69 years.

Abstract: Elderly patients with aggressive lymphoma have an aggressive disease with adverse prognostic parameters at the time of diagnosis. Slightly longer survival was observed for patients treated with an anthracycline-containing regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
86
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(92 citation statements)
references
References 0 publications
5
86
0
1
Order By: Relevance
“…However, of these 12 studies, only 1 directly compared anthracyclinecontaining and non-anthracycline-containing regimens. 10 Two of the 12 studies used mitoxantrone, an anthracenedione originally designed to reduce cardiotoxicity, as a substitute for anthracycline. 11,12 The remaining trials examined the efficacy of reduced-dose regimens, altered chemotherapy schedules, and variations in other regimen components.…”
mentioning
confidence: 99%
“…However, of these 12 studies, only 1 directly compared anthracyclinecontaining and non-anthracycline-containing regimens. 10 Two of the 12 studies used mitoxantrone, an anthracenedione originally designed to reduce cardiotoxicity, as a substitute for anthracycline. 11,12 The remaining trials examined the efficacy of reduced-dose regimens, altered chemotherapy schedules, and variations in other regimen components.…”
mentioning
confidence: 99%
“…This equivalence of survival is despite the fact that the CR rate was less with PMitCEBO and presumably reflects that the earlier response assessment carried out with the shorter duration regimen underestimates the true response rate because of residual necrotic or fibrotic tissue (Surbone et al, 1988;Sweetenham et al, 1991). PMitCEBO is thus a valid alternative to CHOP contrasting with several other curtailed or modified regimens, which appear to be inferior (Meyer et al, 1995;Sonneveld et al, 1995;Bastion et al, 1997;Tirelli et al, 1998;Osby et al, 2003). A decision as to whether to use CHOP or PMitCEBO should therefore be based on the ease of administration and the comparative toxicities of the two regimens.…”
Section: Discussionmentioning
confidence: 92%
“…Advanced age is an independent poor prognostic factor, with inability to tolerate chemotherapy and maintain dose intensity (International NHL Prognostic Factors Project, 1993;NHL Classification Project, 1997;Bastion et al, 1997). Higher treatment-related mortality has also been reported in older patients using the CHOP (cyclophosphamide, doxorubicin, vincristine and prednisolone) regimen (Armitage and Potter, 1984).…”
mentioning
confidence: 99%
“…Their reports demonstrated that the CHOPregimen was well tolerated by patients over 60 years old. Therefore, we prescribed a CHOP-likeregimen as induction chemotherapy, however, the outcome of patients who achieve PR with firstline chemotherapy was still poor in several reports (14,15). The treatment strategy for elderly NHLpatients varies.…”
Section: Discussionmentioning
confidence: 99%